Electrochemical recovery method of retired lithium iron phosphate battery

Through electrochemical oxidation reaction, decommissioned lithium iron phosphate battery positive electrode material is selectively leaching lithium ions, and separated the electrolyte with anion exchange membrane, solving the problems of low lithium extraction rate and high energy consumption in the existing retired lithium iron phosphate battery recycling methods, achieving efficient, environmentally friendly and high-value lithium recycling effects.

CN119612470APending Publication Date: 2025-03-14EAST CHINA UNIV OF SCI & TECH

Patent Information

Application Number
CN202411926762.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing retired lithium iron phosphate battery recycling methods have problems such as low lithium extraction rate, high energy consumption, low recovery rate and large reagent consumption, making it difficult to achieve efficient, environmentally friendly and high-value lithium recycling.

Method used

The decommissioned lithium iron phosphate battery cathode material is decomposed by electrochemical oxidation reaction, and the electrolyte on the anode is oxidized to promote the selective leaching of lithium ions, and the voltage is reduced by using highly oxidative active substances on the cathode, and the anion exchange membrane is used to separate the anode and the cathode side electrolyte to reduce impurity ion exchange.

Benefits of technology

It realizes efficient selective leaching of lithium ions, with lithium recovery rate reaching more than 89%, iron phosphate recovery rate reaching more than 90%, electrochemical reaction voltage decreases, reagent and energy consumption decreases, easy operation, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612470A_ABST
    Figure CN119612470A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery recovery, in particular to an electrochemical recovery method of a retired lithium iron phosphate battery, which comprises the following steps: preparing an electrode and constructing an electrolytic tank; performing an electrochemical leaching lithium extraction reaction and a circulating experiment; lithium precipitation and anode recovery; and regenerating the electrolyte. According to the method, the retired lithium iron phosphate battery electrode material is recycled by adopting an electrochemical selective leaching lithium extraction technology, the recovery rate of lithium can reach 89% or above, the recovery rate of iron phosphate can reach 90% or above, the regeneration rate of an anode side electrolyte and a cathode side electrolyte can reach 95% or above, and the selectivity of lithium leaching can reach 900 or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion battery recycling, and in particular to an electrochemical recycling method for retired lithium iron phosphate batteries. Background Art

[0002] With the growing demand for efficient and green energy technologies, the lithium-ion battery (LIBs) industry has ushered in rapid development. Driven by the active policy, the electric vehicle (EV) market has shown an exponential growth trend. By 2020, EVs have accounted for 52% of the global lithium-ion battery market. As one of the earliest battery technologies used in the industrial field, lithium iron phosphate (LFP) batteries have been widely used in energy storage and power systems due to their advantages such as high safety, low material cost and long cycle life. However, the large loss of lithium during long-term cycles, the accumulation of electrochemical side reactions, the amorphization of the electrode surface structure and the consumption of oxygen eventually lead to the gradual attenuation of the capacity of LFP batteries and their failure and scrapping, with an average service life of only 5-8 years. The toxic compounds in retired LFP batteries, mainly including ethylene carbonate, propylene carbonate, diethyl carbonate and phosphorus pentafluoride in the electrolyte, not only pose a threat to the ecosystem and biological health, but also pollute soil and water resources. As a national strategic resource, the content of lithium in retired LFP batteries is significantly higher than the concentration in ores and brines. As the market demand for lithium iron phosphate batteries continues to grow, expanding their recycling scale will bring significant economic benefits and help ensure national resource security. It is expected that by 2030, the recycling market size of retired LFP batteries will increase from 120 GWh in 2020 to 1500 GWh. Therefore, in the upsurge of recycling retired LFP batteries, it is urgent to develop an environmentally friendly, efficient and high-value selective lithium extraction method to promote its application in industrial production.

[0003] At present, the recycling methods of retired LFP batteries are mainly divided into pyrometallurgy, hydrometallurgy and direct repair method. Pyrometallurgy extracts iron and phosphorus elements by high-temperature treatment of the positive electrode powder of the waste battery, and has the advantages of fast reaction rate, simple operation and large processing capacity. However, this method has the problems of low lithium extraction rate and high energy consumption. For example, CN113430322A discloses a method for recovering phosphorus and iron in waste lithium iron phosphate batteries, by mixing iron phosphate slag, carbonaceous reducing agent and flux, adding a binder, and reducing and smelting in an electric furnace to recover iron and phosphorus elements. This method has the problems of high energy consumption and failure to recover high-value lithium elements. The direct repair method prepares regenerated lithium iron phosphate under high temperature conditions by adding a lithium source, an iron source and a reducing agent to the positive electrode powder, and the process is relatively simple. However, similar to pyrometallurgy, this method also has the problems of high energy consumption, great difficulty in repair and low recovery rate.

[0004] Hydrometallurgy has solved the above problems to a certain extent. This method destroys the chemical structure of the positive electrode material through high concentrations of strong acids (such as HCl, H2SO4, H3PO4) and oxidants (such as H2O2) to achieve oxidation of divalent iron and leaching of lithium ions; subsequently, solvent extraction and precipitation processes are used to grade and recover the metal elements. Wet leaching has the advantages of low energy consumption, mild operating conditions, and low toxic gas emissions. However, this method has the problems of cumbersome processing procedures, limited recovery efficiency, and large amounts of reagents used, which in turn reduces the recovery value of retired LFP batteries. For example, CN116750746A discloses a method for synthesizing lithium iron phosphate using waste electrode pieces from battery factories. By using a large amount of acid, reducing agent, oxidant and chelating agent, the full component recovery of iron, phosphorus and lithium is achieved, but the process is complicated and a large amount of waste liquid is generated, which significantly increases the subsequent processing costs. CN117383588A discloses an electrochemical yin-yang coupled wet recovery technology, which achieves oxidative decomposition of retired lithium iron phosphate batteries by electrolysis. In this method, Fe on the anode 2+ Oxidized to Fe 3+ , which promotes the decomposition of lithium iron phosphate; the H2O2 generated on the cathode reacts with lithium iron phosphate to generate iron phosphate and ·OH, and the self-catalytic effect of ·OH will further improve the recovery rate of lithium. This method has improved the recovery efficiency, but its electrolyte still requires a large amount of acid. In a low pH environment, iron phosphate and lithium iron phosphate are easily dissolved, resulting in a decrease in the recovery rate of iron phosphate products and the purity of lithium carbonate. At the same time, this process also has the problems of high voltage and complex preparation of electrode materials.

[0005] Therefore, in view of the various problems currently encountered in the wet recycling of retired LFP batteries, it is urgent to develop a new method to achieve efficient recycling of retired LFP, which can improve the recovery rate of lithium ions and iron phosphate while shortening the operation steps and reducing the consumption of reagents and energy. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention proposes an electrochemical recovery method for retired lithium iron phosphate batteries, which realizes the decomposition of the positive electrode material of retired lithium iron phosphate batteries through electrochemical oxidation reaction. During the electrochemical reaction, divalent iron ions are oxidized to trivalent iron ions on the anode, which promotes the selective leaching of lithium ions; the substance reacting on the cathode is a substance with high oxidizability and reversibility, which is conducive to reducing the voltage of the electrochemical reaction and the regeneration of the cathode active material after the reaction. At the same time, an anion exchange membrane is used to separate the anode side electrolyte and the cathode side electrolyte to avoid cation exchange between the anode side electrolyte and the cathode side electrolyte, reduce the impurity ions in the anode side electrolyte, and easily realize the regeneration of the anode side electrolyte and the cathode side electrolyte. The method has the advantages of mild conditions, simple operation, high recovery rate, and low reagent and energy consumption.

[0007] The present invention is implemented by the following technical solutions: An electrochemical recovery method for retired lithium iron phosphate batteries, comprising the following steps: 1. Electrode preparation and electrolytic cell construction The cathode powder of retired lithium iron phosphate batteries is wrapped with conductive materials as the anode of the electrode system. If the cathode active material is insoluble in water, the cathode active material is wrapped with conductive materials or directly placed in the electrolyte as the cathode of the electrode system; if the cathode active material is easily soluble in water or is a gas, the conductive material is used as the cathode of the electrode system.

[0008] An anion exchange membrane is used to separate the anode side and the cathode side, electrodes are inserted into the anode side and the cathode side respectively, and electrolyte is added to form a two-electrode leaching system, and the circulation of the electrolyte is achieved by a pump.

[0009] In a preferred embodiment of the present invention, the conductive material includes, but is not limited to, one or more of metal materials (e.g., titanium / silver / copper / aluminum wire, titanium / silver / copper / aluminum mesh, titanium / silver / copper / aluminum plate), alloy materials (e.g., brass, nickel-chromium alloy), inorganic non-metallic materials (e.g., graphite), and polymer conductive materials (e.g., carbon fiber, carbon cloth, carbon felt). There is no limit to the number of layers of conductive material, and the retired lithium iron phosphate battery positive electrode powder can be wrapped with two or more layers of conductive material. For example, the retired lithium iron phosphate battery positive electrode powder can be wrapped with two, three, or four layers of conductive material.

[0010] In a preferred embodiment of the present invention, the cathode active material includes but is not limited to: Silver salts, including but not limited to silver chloride, silver sulfate, silver nitrate, silver oxide; silver (II) salts, including but not limited to silver (II) fluoride, silver (II) sulfate, silver (II) cyanide; silver trioxide; Copper or cuprous salts, including but not limited to cupric chloride, cupric sulfate, cupric nitrate, cupric acetate, cupric oxalate, basic cupric carbonate, cupric phosphate, cupric fluoride, cupric bromide, cupric hydroxide, cuprous chloride, cuprous bromide, cuprous iodide, cuprous oxide, cuprous acetate; Iron salts, including but not limited to ferric chloride, ferric sulfate, ferric nitrate, ferric acetate, ferric oxalate, ferric hydroxide, ferric oxide, ferric fluoride, ferric phosphate, ferric cyanide; Permanganates, including but not limited to potassium permanganate and sodium permanganate; manganese dioxide; Mercury (II) salts, including but not limited to mercuric chloride, mercuric sulfate, mercuric nitrate, mercuric fluoride, mercuric oxide, phenylmercury, mercury (II) acetate, mercury (II) oxychloride; Gold (III) salts, including but not limited to gold chloride, gold bromide, gold sulfate, gold fluoride, gold cyanide, gold acetate, gold nitrate, gold oxide, gold phosphate, and chloroauric acid; Thiosulfate salts, including but not limited to sodium thiosulfate, potassium thiosulfate, copper thiosulfate, ammonium thiosulfate, silver thiosulfate, lead thiosulfate, gold thiosulfate, nickel thiosulfate; Thallium (III) salts, including but not limited to thallium chloride, thallium sulfate, thallium nitrate, thallium fluoride, and thallium oxide; Dichromates, including but not limited to sodium dichromate, potassium dichromate, ammonium dichromate, lead dichromate, copper dichromate, copper ammonium dichromate, manganese dichromate, iron dichromate, and nickel dichromate; Hypochlorites and perchlorates, including but not limited to sodium hypochlorite, potassium hypochlorite, calcium hypochlorite, lithium hypochlorite, ammonium hypochlorite, sodium perchlorate, potassium perchlorate, ammonium perchlorate, aluminum perchlorate, lithium perchlorate, copper perchlorate; Cobalt (III) salts, including but not limited to cobalt trichloride, cobalt trifluoride, cobalt trisulfide, cobalt triperoxide, cobalt trichromate; and cobalt oxide; Lead (IV) salts, including but not limited to lead tetrachloride, lead tetrafluoride, lead oxide, lead sulfide, lead acetate, lead nitrate, and lead chromate; Perbromates, including but not limited to sodium perbromate, potassium perbromate, ammonium perbromate, aluminum perbromate, lithium perbromate, and copper perbromate; Oxidizing gases, including but not limited to oxygen and chlorine; and Elemental iodine, hydrogen peroxide.

[0011] The cathode active material is selected as a substance with high oxidizability, which is beneficial to reducing the voltage of the electrochemical reaction.

[0012] In a preferred embodiment of the present invention, the anion exchange membrane includes but is not limited to AMVN, DSVN, AAM, CAM. The anion exchange membrane only allows anions to pass through, and can effectively separate the anode side and the cathode side, so that no cation exchange occurs between the anode side electrolyte and the cathode side electrolyte.

[0013] In a preferred embodiment of the present invention, the electrolyte on the anode side includes but is not limited to sodium chloride, ammonium chloride, potassium chloride, sodium sulfate, potassium sulfate, ammonium sulfate, and lithium chloride. When the cathode active material is insoluble in water, the electrolyte on the cathode side includes but is not limited to sodium chloride, ammonium chloride, potassium chloride, magnesium chloride, calcium chloride, sodium sulfate, potassium sulfate, and ammonium sulfate; when the cathode active material is easily soluble in water, the electrolyte on the cathode side is a solution of the active material.

[0014] In a preferred embodiment of the present invention, the concentration of the electrolyte is 0.1-5 M, more preferably 0.5-3 M. For example, the concentration of the electrolyte can be 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M, 0.6 M, 0.7 M, 0.8 M, 0.9 M, 1.0 M, 1.2 M, 1.4 M, 1.6 M, 1.8 M, 2.0 M, 2.2 M, 2.4 M, 2.6 M, 2.8 M, 3.0 M, 3.2 M, 3.4 M, 3.6 M, 3.8 M, 4.0 M, 4.2 M, 4.4 M, 4.6 M, 4.8 M, 5.0 M.

[0015] In a preferred embodiment of the present invention, the pH of the electrolyte at the anode side is 4 to 5. At this pH, both lithium iron phosphate and iron phosphate remain stable and do not dissolve.

[0016] In a preferred embodiment of the present invention, the pH of the cathode electrolyte is 1-10. For example, the pH of the cathode electrolyte is 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10.

[0017] In a preferred embodiment of the present invention, the solid-liquid ratio on the anode side (i.e., the ratio of the mass of the retired lithium iron phosphate battery electrode powder on the anode side to the volume of the electrolyte) is 10-80 g / L. For example, the solid-liquid ratio on the anode side is 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L.

[0018] In a preferred embodiment of the present invention, the volume of the electrolyte is 0.1-100 L. For example, the volume of the electrolyte is 0.1 L, 0.2 L, 0.4 L, 0.6 L, 0.8 L, 1.0 L, 1.5 L, 2.0 L, 2.5 L, 3.0 L, 3.5 L, 4.0 L, 4.5 L, 5.0 L, 5.5 L, 6.0 L, 6.5 L, 7.0 L, 7.5 L, 8.0 L, 8.5 L, 9.0 L, 9.5 L, 10 L, 15 L, 20 L, 25 L, 30 L, 35 L, 40 L, 45 L, 50 L, 55 L, 60 L, 65 L, 70 L, 75 L, 80 L, 85 L, 90 L, 95 L, 100 L.

[0019] 2. Electrochemical leaching and lithium extraction reaction and cycle experiment A voltage is applied to the two-electrode leaching system to carry out an electrochemical leaching reaction for lithium extraction.

[0020] The current, voltage and reaction capacity of the reaction are monitored during the entire leaching and lithium extraction reaction process. Preferably, a constant current-constant voltage mode is adopted. The mechanism of the electrochemical leaching and lithium extraction reaction is: Anode: LiFePO4-e - = FePO4+ Li + Cathode: X + e - =X - (X is the cathode active material) In the present invention, the cathode active material is selected to be highly oxidizable and reversible, so that reduction of the cathode active material occurs at the cathode rather than electrolysis of water to produce hydrogen. 3+ / Fe 2+ The standard electrode potential of Cu is 0.771 V. 2 + The standard electrode potential of / Cu is 0.3419 V, I2 / I - The standard electrode potential of is 0.5355 V, the standard electrode potential of AgCl / Ag is 0.2220 V, and the standard electrode potential of H2O / H2 is -0.8277 V, which is much smaller than the standard electrode potential of the cathode active material of the present invention. The applicant has found that by selecting the cathode active material to be highly oxidizing, the voltage of the electrolysis reaction can be greatly reduced, thereby at least reducing the occurrence of side reactions.

[0021] In a preferred embodiment of the present invention, the applied voltage is 0.5-1.2V.

[0022] In a preferred embodiment of the present invention, the current density is 10-40 A / m 2 .

[0023] After one round of electrochemical leaching and lithium extraction reaction is completed, the anode side electrode is replaced and a second round of electrochemical leaching and lithium extraction reaction is carried out to increase the concentration of lithium ions in the electrolyte on the anode side. After multiple rounds of electrochemical leaching and lithium extraction reactions, the lithium ion concentration in the electrolyte can reach 15-25 g / L.

[0024] 3. Lithium precipitation and anode recovery After multiple rounds of electrochemical leaching and lithium extraction reactions, the electrolyte on the anode side is collected, the pH is adjusted to 8-12, and then filtered to remove impurity ions. Solid carbonate and / or bicarbonate is added to the filtrate or CO2 is introduced to form Li2CO3 precipitation, and solid Li2CO3 is obtained after separation.

[0025] In a preferred embodiment of the present invention, the pH is adjusted to 8-12 by sodium hydroxide, potassium hydroxide, ammonia water, or sodium bicarbonate.

[0026] In a preferred embodiment of the present invention, the solid carbonate is sodium carbonate or potassium carbonate, and the solid bicarbonate is one or more of sodium bicarbonate, potassium bicarbonate, and ammonium bicarbonate.

[0027] The residue in the anode side electrode is collected and washed, dried, roasted and floated to obtain a high-purity iron phosphate product.

[0028] Optionally, the method of the present invention further comprises a step of regenerating the electrolyte.

[0029] Anode electrolyte regeneration: Add 1-5 M inorganic acid to the filtrate after separation of Li2CO3 and adjust the solution pH to 4-5 to achieve anode electrolyte regeneration. In a preferred embodiment of the present invention, the inorganic acid may be hydrochloric acid or sulfuric acid.

[0030] Cathode electrolyte regeneration: For highly reducible X - , pass oxygen or add 1-5 M hydrogen peroxide to make X - Oxidation to X, for X with low reducibility or in solid form - , using a three-electrode system, X - As the working electrode, KCl-saturated Ag / AgCl electrode as the reference electrode, titanium mesh as the counter electrode, the regeneration of X was achieved in 0.1-2 M inorganic acid solution.

[0031] The present invention adopts electrochemical selective leaching and lithium extraction technology to recycle retired lithium iron phosphate battery electrode materials, wherein the lithium recovery rate can reach more than 89%, the iron phosphate recovery rate can reach more than 90%, the anode side electrolyte and the cathode side electrolyte regeneration rate can reach more than 95%, and the lithium leaching selectivity can reach more than 900.

[0032] The present invention has the following beneficial effects: (1) The divalent iron in the positive electrode of retired lithium iron phosphate batteries is oxidized to trivalent iron by an electrochemical method, and an anion exchange membrane is added between the anode and cathode sides to achieve selective leaching of lithium and reduce impurity ions in the electrolyte on the anode side, thereby improving the recovery rate of lithium ions and obtaining a high-purity iron phosphate product.

[0033] (2) The pH of the electrolyte on the anode side is 4-5, and there is no need to consume excessive alkali or acid for neutralization; the electrolyte on the anode side and the electrolyte on the cathode side can be recycled and reused, reducing reagent consumption and waste liquid discharge; the concentration of lithium ions in the electrolyte on the anode side is increased by electric drive, which reduces the evaporation and concentration steps compared to traditional recovery methods and greatly reduces energy consumption; the use of highly oxidizing active substances on the cathode side greatly reduces the voltage.

[0034] (3) The device used in the present invention has a simple structure, is easy to operate, and has a low time cost; the operation process has low energy consumption; the raw materials are widely available and inexpensive; the solid-liquid ratio is greatly improved, the production efficiency is high, and it can be widely used in industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 In Example 1, Comparative Example 1 and Comparative Example 2, the pH of the electrolyte on the anode side is 4, the solid-liquid ratio is 10 g / L, and the current density is 20 A / m 2 Lithium leaching rate, current efficiency and iron dissolution rate under different voltages under different conditions.

[0036] Figure 2 This is the species distribution diagram of divalent iron (a) and trivalent iron (b) in a high-salt system at room temperature.

[0037] Figure 3 The voltage of Example 1, Comparative Example 3 and Comparative Example 4 is 0.6 V, the solid-liquid ratio is 10 g / L, and the current density is 20 A / m 2 Lithium leaching rate, current efficiency and iron dissolution rate at different anode side electrolyte pH under different conditions.

[0038] Figure 4 The results of Examples 2, 3, 4 and 5 were as follows: the voltage was 0.6 V, the pH of the electrolyte on the anode side was 5, and the current density was 40 A / m 2 Lithium leaching rate, current efficiency and iron dissolution rate under different solid-liquid ratios under different conditions.

[0039] Figure 5 It is a kinetic diagram of the lithium leaching rate of Examples 2, 3, 4 and 5 as the reaction progresses.

[0040] Figure 6 The lithium leaching rate, current efficiency and iron dissolution rate at different current densities of Examples 5, 6 and 7 under the conditions of a voltage of 0.6 V and a solid-to-liquid ratio of 50 g / L. DETAILED DESCRIPTION

[0041] In order to better explain the present invention, the present invention is further described in conjunction with the following specific embodiments, but the present invention is not limited to the following specific embodiments.

[0042] Unless otherwise specified, the methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0043] Example 1 A method for electrochemically recovering retired lithium iron phosphate batteries comprises the following steps: 1. Electrode preparation and electrolytic cell construction The retired lithium iron phosphate battery positive electrode powder (Fe accounts for about 34.3% by mass and Li accounts for about 4.26% by mass) is wrapped with carbon cloth as the anode of the electrode system.

[0044] The anode side and cathode side were separated by anion exchange membrane DSVN. A sandwich structure electrode was inserted into the anode side and sodium sulfate was added as the electrolyte. A titanium plate was inserted into the cathode side as the electrode and iron sulfate solution was added as the electrolyte. The electrolyte concentration on the anode side was 0.5 M, pH was 4, and the volume was 0.15 L. The electrolyte concentration in the cathode tank was 0.5 M, pH was 1, and the volume was 0.15 L. The solid-liquid ratio on the anode side was 10 g / L. The peristaltic pump speed was 500 rpm. The electrode area was 40 cm 2 .

[0045] 2. Electrochemical leaching and lithium extraction reaction and cycle experiment A voltage of 0.6 V was applied for electrochemical lithium leaching reaction, and the current density was 20 A / m 2 .

[0046] After one round of electrochemical leaching and lithium extraction reaction, the anode side electrode was replaced and a second round of electrochemical leaching and lithium extraction reaction was performed. After 47 rounds of electrochemical leaching and lithium extraction reaction, the lithium ion concentration in the electrolyte of the anode tank was 19.0 g / L.

[0047] 3. Lithium precipitation and anode recovery After the electrochemical leaching reaction is completed, the electrolyte on the anode side is collected. Solid sodium hydroxide is added to the electrolyte on the anode side to adjust the solution pH to 10, and impurity ions are removed by filtration. The filtrate is then mixed with solid sodium carbonate in equal proportions to form Li2CO3, which is then filtered to obtain solid Li2CO3.

[0048] The residue in the anode side electrode is collected and washed, dried, roasted and floated to obtain a high-purity iron phosphate product.

[0049] 4. Electrolyte regeneration Regeneration of the anode side electrolyte: Add 1 M sulfuric acid to the filtrate from which Li2CO3 is separated, adjust the solution pH to 4, and regenerate to obtain the anode side electrolyte.

[0050] Regeneration of cathode electrolyte: 1 M sulfuric acid is added to the cathode electrolyte after the reaction to maintain the pH of the solution at 1, and oxygen is introduced to oxidize the divalent iron ions in the solution to trivalent iron ions, thereby regenerating the cathode electrolyte.

[0051] Finally, Li + Recovered in the form of Li2CO3, Li +The recovery rates of FePO4 and FePO4 were 89.1% and 92.9% respectively. In one round of leaching, the lithium leaching rate was 94.9%, the iron dissolution rate was 0.10%, the current efficiency was 112%, the reaction time was 4.13h, and the lithium leaching selectivity was 949.

[0052] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that a voltage of 0.4 V is applied to perform the electrochemical leaching and lithium extraction reaction.

[0053] Finally, Li + Recovered in the form of Li2CO3, Li + The recovery rates of FePO4 and FePO4 were 84.2% and 90.2% respectively. In one round of leaching, the leaching rate of lithium was 93.5%, the dissolution rate of iron was 1.5%, the current efficiency was 102%, the reaction time was 5.04h, and the lithium leaching selectivity was 62.3. Compared with Example 1, the leaching rate and current efficiency of lithium were reduced, mainly because the lower voltage caused the deeper lithium ions on the anode side electrode to be unable to escape from the lithium iron phosphate electrode powder. At the same time, a longer leaching time was required to achieve the theoretical reaction capacity. Since the current was maintained at a lower range of 2-5 mA for a long time, it was easy to cause the dissolution of iron ions and the reduction of lithium leaching selectivity.

[0054] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that a voltage of 0.8 V is applied to perform the electrochemical leaching and lithium extraction reaction.

[0055] Finally, Li + Recovered in the form of Li2CO3, Li + The recovery rates of FePO4 and FePO4 were 80.1% and 86.2% respectively. In one round of leaching, the leaching rate of lithium was 89.0%, the dissolution rate of iron was 1.0%, the current efficiency was 91.5%, the reaction time was 4.28h, and the lithium leaching selectivity was 89.0. Compared with Example 1, the leaching rate and current efficiency of lithium were significantly reduced, which may be due to the occurrence of side reactions on the anode side electrode caused by the higher voltage.

[0056] from Figure 1 It can be seen that on the anode side, the electrolyte pH is 4, the cathode active material is ferric sulfate, the solid-liquid ratio is 10 g / L, and the current density is 20 A / m 2 Under the same conditions, a voltage of 0.6 V is more conducive to improving the selective leaching of lithium from retired lithium iron phosphate battery electrode powder and the recovery of iron phosphate.

[0057] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the pH of the electrolyte on the anode side is 2.

[0058] Finally, Li+ Recovered in the form of Li2CO3, Li + The recovery rates of FePO4 and FePO4 were 82.3% and 83.1% respectively. In one round of leaching, the leaching rate of lithium was 95.3%, the dissolution rate of iron was 10.5%, the current efficiency was 111.5%, the reaction time was 4.47 h, and the lithium leaching selectivity was 9.08. Compared with Example 1, the dissolution rate of iron increased by more than 100 times, and the lithium leaching selectivity was significantly reduced. Therefore, in the impurity removal step before lithium precipitation, iron ions will precipitate in the form of iron phosphate / lithium iron phosphate / ferric hydroxide / ferrous hydroxide, increasing the loss of lithium, reducing the total recovery rate of lithium, and greatly reducing the selectivity of the lithium leaching process.

[0059] In order to study the reasons for the significant decrease in lithium leaching selectivity, the applicant drew a species distribution diagram of divalent iron at different pH in a room temperature high salt system, such as Figure 2 As shown in (a). It can be seen that when the pH is less than 4, the divalent iron mainly exists in the form of ions, resulting in a great dissolution of the iron in the lithium iron phosphate; when the pH is not less than 4, the lithium iron phosphate can exist stably. Figure 2 The species distribution diagram of divalent iron shown in (a) further analyzes from a theoretical perspective the reason why the lithium leaching selectivity is significantly reduced when the pH is 2.

[0060] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the pH of the electrolyte on the anode side is 6.

[0061] Finally, Li + Recovered in the form of Li2CO3, Li + The recovery rates of FePO4 and FePO4 were 77.8% and 82.4% respectively. In one round of leaching, the leaching rate of lithium was 84.6%, the dissolution rate of iron was 0.48%, the current efficiency was 94.4%, the reaction time was 4.32h, and the lithium leaching selectivity was 176. Compared with Example 1, the lithium leaching rate and current efficiency were significantly reduced.

[0062] In order to study the reasons for the reduction of lithium leaching rate and current efficiency, the applicant drew a species distribution diagram of trivalent iron at different pH in a room temperature high salt system, such as Figure 2As shown in (b). It can be seen that when the pH is greater than 5, iron phosphate tends to be converted into iron hydroxide, thereby generating trace amounts of iron hydroxide on the electrode surface, reducing the contact area between the electrode and the solution, and thus hindering the diffusion of lithium ions, reducing the current efficiency of the electrochemical oxidation leaching process, and reducing the lithium leaching rate. From theoretical analysis and experimental results, when the pH of the electrolyte on the anode side is less than 4, lithium iron phosphate will dissolve, and the amount of dissolution will increase as the pH decreases; when the pH is greater than 5, iron phosphate is easily converted into iron hydroxide, and the amount of conversion increases as the pH increases. Under the conditions of pH 4-5, both iron phosphate and lithium iron phosphate can remain stable.

[0063] By comparing the lithium leaching rate, current efficiency and iron dissolution rate of Example 1, Comparative Example 3 and Comparative Example 4, it can be concluded that when the voltage is 0.6 V, the solid-liquid ratio is 10 g / L and the current density is 20 A / m 2 Under the following conditions, when the pH of the electrolyte on the anode side is 4, the comprehensive recovery effect of the positive electrode powder of retired lithium iron phosphate batteries is optimal.

[0064] Example 2 A method for electrochemically recovering retired lithium iron phosphate batteries comprises the following steps: 1. Electrode preparation and electrolytic cell construction The retired lithium iron phosphate battery positive electrode powder (Fe accounts for about 34.3% by mass and Li accounts for about 4.26% by mass) is wrapped with carbon cloth as the anode of the electrode system.

[0065] The anode side and cathode side were separated by anion exchange membrane AMVN. A sandwich structure electrode was inserted into the anode side and potassium sulfate was added as the electrolyte. A titanium plate was inserted into the cathode side as the electrode and iron sulfate solution was added as the electrolyte. The electrolyte concentration on the anode side was 1 M, pH 5, and the volume was 0.15 L. The electrolyte concentration in the cathode tank was 1 M, pH 1, and the volume was 0.15 L. The solid-liquid ratio on the anode side was 10 g / L. The peristaltic pump speed was 800 rpm. The electrode area was 40 cm 2 .

[0066] 2. Electrochemical leaching and lithium extraction reaction and cycle experiment A voltage of 0.6 V was applied for electrochemical lithium leaching reaction, and the current density was 40 A / m 2 .

[0067] After one round of electrochemical leaching and lithium extraction reaction, the anode side electrode was replaced and a second round of electrochemical leaching and lithium extraction reaction was carried out. After 47 rounds of electrochemical leaching and lithium extraction reaction, the lithium ion concentration in the electrolyte of the anode tank was 19.1 g / L.

[0068] 3. Lithium precipitation and anode recovery After the electrochemical leaching reaction is completed, the electrolyte on the anode side is collected. Solid sodium hydroxide is added to the electrolyte on the anode side to adjust the solution pH to 10, and impurity ions are removed by filtration. The filtrate is then mixed with solid sodium carbonate in equal proportions to form Li2CO3, which is then filtered to obtain solid Li2CO3.

[0069] The residue in the anode side electrode is collected and washed, dried, roasted and floated to obtain a high-purity iron phosphate product.

[0070] 4. Electrolyte regeneration Regeneration of the anode side electrolyte: Add 1 M sulfuric acid to the filtrate from which Li2CO3 is separated, adjust the solution pH to 5, and regenerate to obtain the anode side electrolyte.

[0071] Regeneration of cathode electrolyte: 1 M sulfuric acid is added to the cathode electrolyte after the reaction to maintain the pH of the solution at 1, and oxygen is introduced to oxidize the divalent iron ions in the solution to trivalent iron ions, thereby regenerating the cathode electrolyte.

[0072] Finally, Li + Recovered in the form of Li2CO3, Li + The recovery rates of FePO4 and FePO4 were 89.4% and 93.2% respectively. In one round of leaching, the lithium leaching rate was 95.1%, the iron dissolution rate was 0.02%, the current efficiency was 110%, the reaction time was 2.01h, and the lithium leaching selectivity was 4755.

[0073] Example 3 The difference between Example 3 and Example 2 is that the solid-liquid ratio on the anode side is 20 g / L, and the number of leaching cycles is 23 times.

[0074] Finally, Li + Recovered in the form of Li2CO3, Li + The recovery rates of FePO4 and FePO4 were 90.1% and 94.0% respectively. In one round of leaching, the lithium leaching rate was 95.9%, the iron dissolution rate was 0.02%, the current efficiency was 106%, the reaction time was 3.86h, and the lithium leaching selectivity was 4795.

[0075] Example 4 The difference between Comparative Example 4 and Example 2 is that the solid-liquid ratio on the anode side is 30 g / L and the number of leaching cycles is 16 times.

[0076] Finally, Li + Recovered in the form of Li2CO3, Li +The recovery rates of FePO4 and FePO4 were 89.3% and 93.1% respectively. In one round of leaching, the lithium leaching rate was 95.0%, the iron dissolution rate was 0.05%, the current efficiency was 105%, the reaction time was 5.56h, and the lithium leaching selectivity was 1900.

[0077] Example 5 The difference between Example 5 and Example 2 is that the solid-liquid ratio on the anode side is 50 g / L and the number of cyclic leaching times is 10 times.

[0078] Finally, Li + Recovered in the form of Li2CO3, Li + The recovery rates of FePO4 and FePO4 were 89.1% and 92.8% respectively. In one round of leaching, the leaching rate of lithium was 94.8%, the dissolution rate of iron was 0.08%, the current efficiency was 98.0%, the reaction time was 9.03h, and the lithium leaching selectivity was 1185. Compared with Example 2, although the leaching rate and current efficiency of lithium were reduced, the recovery efficiency (i.e., the amount of positive electrode powder that can be recovered per unit time) was improved.

[0079] from Figure 4 It can be seen that as the solid-liquid ratio increases, the iron dissolution rate is still below 0.1%, and the current efficiency is higher than 95%. Figure 5 From the kinetic diagram of the lithium leaching rate changing with the reaction progress, it can be seen that under the four solid-liquid ratio conditions, the lithium leaching kinetics are generally basically the same. Among them, in the first half of the reaction (before the reaction progress is 0.4), the lithium leaching rates corresponding to the solid-liquid ratios of 30 g / L and 50 g / L are higher than those of the other two solid-liquid ratios. Although the electrode thickness of the high solid-liquid ratio is greater, the difficulty of lithium leaching increases, the lithium leaching rate decreases, and the iron dissolution rate increases, the current efficiency and lithium leaching rate remain very high, the iron dissolution rate is below 0.10%, and the high solid-liquid ratio is conducive to reducing the number of cycles, improving the recovery efficiency, and shortening the time to replace the electrode. The solid-liquid ratios of 10 g / L - 50 g / L in Examples 2-5 are all applicable.

[0080] Example 6 The difference between Example 6 and Example 5 is that the current density is 20 A / m 2 .

[0081] Finally, Li + Recovered in the form of Li2CO3, Li + The recovery rates of FePO4 and FePO4 were 90.9% and 94.7% respectively. In one round of leaching, the lithium leaching rate was 96.7%, the iron dissolution rate was 0.04%, the current efficiency was 99.3%, the reaction time was 19.5h, and the lithium leaching selectivity was 2418.

[0082] Example 7 The difference between Example 7 and Example 5 is that the current density is 10 A / m 2 .

[0083] Finally, Li + Recovered in the form of Li2CO3, Li + The recovery rates of FePO4 and FePO4 were 91.5% and 95.3% respectively. In one round of leaching, the leaching rate of lithium was 97.3%, the dissolution rate of iron was 0.05%, the current efficiency was 100%, the reaction time was 46.27h, and the lithium leaching selectivity was 1946. From the comparison of Examples 5, 6 and 7, it can be seen that the reduction of current density slightly increased the current efficiency and lithium leaching rate, slightly reduced the iron dissolution rate, but significantly increased the leaching time. Therefore, increasing the current density greatly increases the leaching efficiency and shortens the leaching time by nearly 4 / 5. On the whole, under the conditions of voltage of 0.6 V and solid-liquid ratio of 50 g / L, the high current density of 40 A / m 2 It is more suitable for the recycling of large quantities of retired lithium iron phosphate battery positive electrode powder.

[0084] Ultimately, under high current density, the lithium leaching rate reached over 94%, and the lithium leaching selectivity reached over 900. At the same time, the recovery rates of lithium ions and iron phosphate remained very high.

[0085] The above description is only a specific embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent transformation made by the present invention, or directly or indirectly applied in other related technical fields, is also included in the patent protection scope of the present invention.

[0086] For the specific conditions not specified in the examples, the conventional conditions or the conditions recommended by the manufacturer were followed. For the reagents or instruments used without specifying the manufacturer, they were all conventional products that can be purchased commercially.

Claims

1. An electrochemical recovery method for retired lithium iron phosphate batteries, characterized in that: The following steps are involved: (1) Electrode preparation and electrolytic cell construction The cathode powder of retired lithium iron phosphate batteries is wrapped with conductive materials as the anode of the electrode system; If the cathode active material is insoluble in water, the cathode active material is wrapped with a conductive material or directly placed in an electrolyte to serve as the cathode of the electrode system; If the cathode active material is easily soluble in water or is a gas, the conductive material is used as the cathode of the electrode system; An anion exchange membrane is used to separate the anode side and the cathode side, and electrodes are inserted into the anode side and the cathode side respectively and electrolyte is added to form a two-electrode leaching system; (2) Electrochemical leaching reaction and cycle experiment Applying voltage to the two-electrode leaching system to perform an electrochemical leaching reaction for lithium extraction; after one round of electrochemical leaching reaction for lithium extraction is completed, replacing the anode side electrode to perform the next round of electrochemical leaching reaction for lithium extraction; (3) Lithium precipitation and anode recovery After the electrochemical leaching reaction is completed, the electrolyte on the anode side is collected, the pH is adjusted to 8-12, and then filtered to remove impurity ions, solid carbonate and / or bicarbonate is added to the filtrate or CO2 is introduced to form Li2CO3 precipitation, and solid Li2CO3 is obtained after separation; The residue in the anode side electrode is collected and washed, dried, roasted and floated to obtain a high-purity iron phosphate product.

2. The method according to claim 1, characterized in that Conductive materials include metal materials, alloy materials, inorganic non-metallic materials, and polymer conductive materials.

3. The method according to claim 2, characterized in that Metal materials include titanium wire, titanium mesh, titanium plate, silver wire, silver mesh, silver plate, copper wire, copper mesh, copper plate, aluminum wire, aluminum mesh, aluminum plate; Alloy materials include brass and nickel-chromium alloy; Inorganic non-metallic materials include graphite; Polymer conductive materials include carbon fiber, carbon cloth, and carbon felt.

4. The method according to claim 3, characterized in that Cathode active material Silver salts, including silver chloride, silver sulfate, silver nitrate, silver oxide; silver (II) salts, including silver (II) fluoride, silver (II) sulfate, silver (II) cyanide; silver trioxide; Copper or cuprous salts, including cupric chloride, cupric sulfate, cupric nitrate, cupric acetate, cupric oxalate, basic cupric carbonate, cupric phosphate, cupric fluoride, cupric bromide, cupric hydroxide, cuprous chloride, cuprous bromide, cuprous iodide, cuprous oxide, cuprous acetate; Iron salts, including ferric chloride, ferric sulfate, ferric nitrate, ferric acetate, ferric oxalate, ferric hydroxide, ferric oxide, ferric fluoride, ferric phosphate, and ferric cyanide; Permanganates, including potassium permanganate and sodium permanganate; manganese dioxide; Mercury (II) salts, including mercuric chloride, mercuric sulfate, mercuric nitrate, mercuric fluoride, mercuric oxide, phenylmercury, mercury (II) acetate, mercury (II) oxychloride; Gold (III) salts, including gold chloride, gold bromide, gold sulfate, gold fluoride, gold cyanide, gold acetate, gold nitrate, gold oxide, gold phosphate, and chloroauric acid; Thiosulfates, including sodium thiosulfate, potassium thiosulfate, copper thiosulfate, ammonium thiosulfate, silver thiosulfate, lead thiosulfate, gold thiosulfate, and nickel thiosulfate; Thallium (III) salts, including thallium chloride, thallium sulfate, thallium nitrate, thallium fluoride, and thallium oxide; Dichromates, including sodium dichromate, potassium dichromate, ammonium dichromate, lead dichromate, copper dichromate, copper ammonium dichromate, manganese dichromate, iron dichromate, and nickel dichromate; Hypochlorites and perchlorates, including sodium hypochlorite, potassium hypochlorite, calcium hypochlorite, lithium hypochlorite, ammonium hypochlorite, sodium perchlorate, potassium perchlorate, ammonium perchlorate, aluminum perchlorate, lithium perchlorate, and copper perchlorate; Cobalt (III) salts, including cobalt trichloride, cobalt trifluoride, cobalt trisulfide, cobalt triperoxide, cobalt trichromate; and cobalt oxide; Lead (IV) salts, including lead tetrachloride, lead tetrafluoride, lead oxide, lead sulfide, lead acetate, lead nitrate, and lead chromate; Perbromates, including sodium perbromate, potassium perbromate, ammonium perbromate, aluminum perbromate, lithium perbromate, and copper perbromate; Oxidizing gases, including oxygen and chlorine; as well as Elemental iodine, hydrogen peroxide.

5. The method according to claim 1, characterized in that The anion exchange membrane includes any one of AMVN, DSVN, AAM, and CAM.

6. The method according to claim 1, characterized in that The electrolyte on the anode side includes sodium chloride, ammonium chloride, potassium chloride, sodium sulfate, potassium sulfate, ammonium sulfate, and lithium chloride; When the cathode active material is insoluble in water, the cathode side electrolyte includes sodium chloride, ammonium chloride, potassium chloride, magnesium chloride, calcium chloride, sodium sulfate, potassium sulfate, and ammonium sulfate; when the cathode active material is easily soluble in water, the cathode side electrolyte is a solution of the active material; The concentration of the electrolyte is 0.1-5M, the pH of the electrolyte on the anode side is 4-5, and the pH of the electrolyte on the cathode side is 1-10.

7. The method according to claim 1, characterized in that The solid-liquid ratio on the anode side is 10-50g / L.

8. The method according to claim 1, characterized in that The voltage is 0.5-1.2V and the current density is 10-40A / m 2 .

9. The method according to claim 1, characterized in that: Adjust pH to 8-12 with sodium hydroxide, potassium hydroxide, ammonia, and sodium bicarbonate; Solid carbonate is sodium carbonate or potassium carbonate, The solid bicarbonate is one or more of sodium bicarbonate, potassium bicarbonate and ammonium bicarbonate.

10. The method according to claim 1, characterized in that Also includes Anode side electrolyte regeneration: add 1-5M inorganic acid to the filtrate after separation of Li2CO3 and adjust the solution pH to 4-5 to achieve anode side electrolyte regeneration; Cathode electrolyte regeneration: For highly reducible X - , pass oxygen or add 1-5 M hydrogen peroxide to make X - Oxidation to X, for X with low reducibility or in solid form - , using a three-electrode system, X - As the working electrode, KCl-saturated Ag / AgCl electrode as the reference electrode, titanium mesh as the counter electrode, the regeneration of X was achieved in 0.1-2M inorganic acid solution.

Citation Information

Patent Citations

  • Method for recycling decommissioned lithium iron phosphate battery by electrochemical negative and positive coupling wet process

    CN117383588A

Cited By

  • Silicate mineral flotation regulator system and application thereof

    CN122183807A

  • Method for removing impurities from lithium carbonate lithium precipitation mother liquor

    CN122520094A